2007
DOI: 10.1007/s10584-006-9196-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in maximum, minimum and mean annual air temperatures across the Northwestern Himalaya during the twentieth century

Abstract: The study reveals significant rise in air temperature in the northwest Himalayan (NWH) region by about 1.6°C in the last century, with winters warming at a faster rate. The diurnal temperature range (DTR) has also shown a significantly increasing trend. This appears to be due to rise in both the maximum as well as minimum temperatures, with the maximum increasing much more rapidly. The results are in contrast to the findings in the Alps and Rockies where the minimum temperatures have increased at an elevated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
235
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 506 publications
(263 citation statements)
references
References 55 publications
26
235
2
Order By: Relevance
“…The result highlights a moderate but long and important coupling between NH warming and TP temperature in the period 1901-1960 ( Figure 4A). This outcome is supported by a previous study performed by Bhutiyani et al (2007) indicating, for the 20th century, similar epochs of temperature variation between global and northwestern Himalayas. Nowadays, although a coupling in the northwestern area of the TP appears clearly and with certain persistence and it can be related to global warming, at the same time, on the rest of southeastern region across the Pyramid AWS, the unvarying TP temperature with NH warming is an unexpected and hard-to-figure behaviour (Figure 4).…”
Section: Warming Trendssupporting
confidence: 89%
“…The result highlights a moderate but long and important coupling between NH warming and TP temperature in the period 1901-1960 ( Figure 4A). This outcome is supported by a previous study performed by Bhutiyani et al (2007) indicating, for the 20th century, similar epochs of temperature variation between global and northwestern Himalayas. Nowadays, although a coupling in the northwestern area of the TP appears clearly and with certain persistence and it can be related to global warming, at the same time, on the rest of southeastern region across the Pyramid AWS, the unvarying TP temperature with NH warming is an unexpected and hard-to-figure behaviour (Figure 4).…”
Section: Warming Trendssupporting
confidence: 89%
“…Analysis of the Mekong River showed that an average flood most likely decreased though there was an increase in the likelihood of extreme floods during the second half of the 20th century 41 . Bhutiyani et al 42,43 reported increasing/decreasing trends over the last 40 years in four river basins of the northwestern Himalaya.…”
Section: Observed Changes In High Flows In Riversmentioning
confidence: 97%
“…Of particular note is the large trans-national Satluj basin, which drains from glaciated headwaters in Tibet into Himachal Pradesh. An increase in mean annual air temperature of 1.6°C has been measured across the north-western Himalayan region during the past century, which is far in excess of mean global warming (Bhutiyani et al 2007).…”
Section: Study Region and Baseline Datamentioning
confidence: 99%